Exploring the Influence of Self-Control, Subjective Well-Being, Happiness, and Life Satisfaction on Prosocial Behavior among Muslim Students in Indonesia - Hidayah, Rifa; Solichah, Novia; Chiedu, Chiedu; Jannah, Miftakhul; Mu’awanah, Elfi; Bukhori, Baidi; Mazaya, Syifa Naja Kamalul (Islamic Guidance and Counseling Journal, 2026)
Prosocial behavior voluntary actions intended to benefit others plays a vital role in adolescents’ social skills, emotional well-being, and constructive interpersonal relationships. Adolescents with high prosociality tend to exhibit lower negative emotions and stronger social development. However, limited research has examined this phenomenon among Muslim university students. Guided by Domain Theory, this study investigates the influence of self-control, subjective well-being, happiness, and life satisfaction on prosocial behavior in Indonesian Muslim students. A cross-sectional design with convenience sampling recruited 300 Muslim university students (84 males, 28%; 216 females, 72%) aged 17–24 years (M = 19, SD = 1.23). Participants completed the Prosocial Tendencies Measure (PTM), Brief Self-Control Scale (BSCS), BBC Subjective Well-being Scale (BBC-SWB), Orientation to Happiness Scale (OTH), and Satisfaction with Life Scale (SWLS), all adapted to the Indonesian context with acceptable reliability. Data were analyzed using multiple linear regression. Results showed that subjective well-being (β = -0.169, p = 0.031) and happiness (β = 0.498, p = 0.000) significantly influenced prosocial behavior. Self-control (β = -0.058, p = 0.333) and life satisfaction (β = 0.119, p = 0.081) showed no significant effect. Indonesian Muslim students who reported higher levels of subjective well-being and happiness were more likely to engage in prosocial behavior. However, the research model hasn’t optimally explained the relationship between variables, as there are still other factors that can influence them.